PENCAK SILAT NURUL HUDA PERKASYA DI TEBUIRENG JOMBANG TAHUN 1982-2019 - Jauharul Ifadhi (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2021)
Abstract: This article aims to explore the historicity of Pencak Silat Nurul Huda Perkasya at the Tebuireng Jombang Islamic Boarding School in the 1982-2019 period. This research is interesting to examine its development because there is a kind of marriage element between artistic culture and santri customs that are thick with Islamic religious values. There are two methods that the authors apply to this study, namely the ethnographic method and the historical research method. The approach chosen is a cultural anthropological approach, while Radcliffe Brown's functional theory is used as an analytical tool. This research resulted in the following conclusions: 1) The relationship between Islamic boarding schools and pencak silat is closely related to the process of establishing a pesantren and as a training ground for soldiers, residents and students to fight against colonialism; 2) The History and Development of Pencak Silat Nurul Huda Perkasya at the Tebuireng Islamic Boarding School from 1982-2019 experienced good development during its 37th year of development not only on the island of Java, but outside Java as well; 3) The function of Pencak Silat Nurul Huda Perkasya in the life of the Tebuireng Islamic Boarding School has 7 functions including: the function of self-defense, the function of the arts, the function of entertainment, the function of sports, the function of religion, the function of education and social functions that can be felt by all members and in general the community. Keywords: Pencak Silat Nurul Huda, Tebuireng, history and development